Pengaruh bahasa Inggris ragam lisan guru, media, dan sumber belajar terhadap kemampuan listening comprehension siswa - Oktarini, Eka; Suyata, Pujiyati (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2019)
Penelitian ini memiliki tujuan yakni untuk mengetahui pengaruhintensitas penggunaan bahasa Inggris ragam lisan,pemanfaatan media pembelajaran,dan kelengkapan sumber belajar terhadap kemampuan listening comprehensionsiswa SMP di Kabupaten Sleman. Penelitian ini adalah penelitian Ex post Facto. Sampel yang dipilih sebanyak 370 siswa, dengan menggunakan teknik stratified proportional cluster random sampling. Instrumen penelitian menggunakan angket dan tes. Kualitas intrumen yang digunakan adalah IRT dengan menggunakan program QUEST. Data dianalisis dengan teknik statistik Regresi Ganda yang diteruskan dengan Korelasi Parsial.Hasil penelitian menunjukkan bahwa penggunaan bahasa Inggris ragam lisan, intensitas pemanfaatan media,dan kelengkapan sumber belajar mempengaruhi kemampuan listening comprehension Siswa SMP di Kabupaten Sleman dengan nilai analisis Regresi (F = 0,038p ≤ 0,05). Pengaruh penggunaan bahasa Inggris ragam lisan terhadap kemampuan listening comprehensionadalah sebesar 12,6 % dengan nilai Korelasi Parsial (r = 0,126, sig. p ≤ 0,05, Beta 0,126).PengaruhIntensitas pemanfaatan media terhadap kemampuan listening comprehensionadalah sebesar 0,8% dengan nilai Korelasi Parsial (r = - 0,080,Sig. p ≤ 0,05, Beta -0,080). Dan pengaruh kelengkapan sumber terhadap kemampuan listening comprehension sebesar 1,4% dengan nilai Korelasi Parsial (r = -0,014, Sig. p ≤ 0,05 Beta -0,014). The effect of teachers’ spoken English variety, media, and learning sources on the ability of students’ listening comprehension AbstractThis study has fourobjectives. First is to investigate the gathering effect of of English spoken language, the intensity of the use of media, and completeness of learning resources on the ability of listening comprehension in Sleman Junior high school students. The other objectives are the effect of each variable on the ability of listening comprehension Junior high school students in Sleman District.This research is an ex-post facto research.The sample consisted of 370 students were selected using stratified proportional random sampling techniques. The research instruments were questionnaire and tests. IRT was used to know the quality of instrumen by using QUEST program. The data were analyzed by using the Multiple Regression and Partial Correlation statistic analysis.The result of analysis indicates that the use of English spoken language, the intensity of the use of media, and completeness of learning resources together combined affect the listening comprehension.with Reression value (F = 0.038, sig. with p ≤ 0.05). The result of each variable on the listening comprehension indicates that the use of English spoken language affects 12.6 % with score (r = 0.126, sig. p ≤ 0.05, Beta 0.126). the intensity of using media affects 0.8% with score (r = - 0.080,Sig. p ≤ 0.05, Beta -0.080).And completeness of learning resources affect 1.4% with score (r = -0.014, Sig. p ≤ 0.05 Beta -0.014).